The science and practice of body composition assessment - McInnis, kyle; American College of Sports Medicine; Monterey Bay Video Production Co. (New York : Monterey Bay Video Production Co., 1999)
Presents a comprehensive overview of both the scientific background and the practical applications of body composition assessment. Includes film footage of actual laboratory and field body composition measurements. Topics include underwater weighing; dual energy X-ray absorptiometry; plethysmography (Bod Pod); skinfold measurements; circumference measurements; bioelectrical impedance; near-infrared interactance (Futrex); and Body Mass Index (BMI)
Title from title screen
Keywords: Body composition -- Measurement; Anthropometry; Adipose tissue; Body weight; Physical fitness